In vitro evaluation of Bifidobacterium strains of human origin for probiotics functional foods - Sousa, T.C. (2013)
The present work investigates some in vitro properties of four strains of bifidobacteria isolated from feces of healthy children (Bifidobacterium longum 51A, B. breve 1101A, B. pseudolongum 1191A and B. 1622A). In vitro tests were carried out to compare growth rate, aerotolerance, antagonistic activity against pathogens, antimicrobial susceptibility profile and cell wall hydrophobicity. Mean doubling time of B. longum 51A was shorter compared to the other strains. All strains were aerotolerant up to 72 hours of exposure to oxygen. In vitro antagonism showed that B. longum 51A and B. pseudolongum 1191A were able to produce inhibitory metabolites against all pathogenic bacteria tested. B. longum 51A was sensitive to the antimicrobials tested, except to neomycin. The hydrophobic property of the cell wall was higher for B. bifidum 1622A. Based on these parameters, B. longum 51A showed the biggest potential for probiotic use among tested strains, presenting the greatest sensitivity to antimicrobials, the best growth rate and the highest capacity to produce antagonistic substances against various pathogenic microorganisms.